Medium-Term Patient-Reported Outcomes after Surgical Management of Perilunate Injury: A Multiinstitutional Experience - Gabig, Andrew M.; Payne, Samuel H.; Whitsett, Adam; Kebede, Sara; Patel, Avani A.; Knaus, William; Ghareeb, Paul (Journal of Wrist Surgery, 2024)
There is a lack of consensus on the optimal treatment of perilunate injuries (PLIs). Open reduction with internal fixation with scapholunate (SL) ligament repair is recommended; however, procedures such as lunotriquetral (LT) ligament repair, carpal tunnel release (CTR), proximal row carpectomy, denervation, and arthrodesis may also be used.The purpose of this study was to assess patient-reported outcomes (PROs) after surgical management of PLIs.A retrospective review of surgically treated PLIs at two institutions in a major metropolitan city from 2014 to 2020 was conducted. Demographics, radiographic data, and details of surgical management were reviewed. PROs were prospectively collected and analyzed.Eighty-seven patients with surgically managed PLIs were identified. The average time to surgery was 4 ± 7days. Twenty-six percent of patients presented with acute median neuropathy. Thirty-seven patients provided PROs for analysis. Patient-Rated Wrist Evaluation scores were 22 ± 12.9, 14.4 ± 11.3, and 37 ± 22 for pain, function, and total scores, respectively. Satisfaction was 7 ± 3 Sixteen percent of patients were unable to maintain employment due to their injury. The interval to return to work was 6.3 ± 7.7 months.PLIs cause significant morbidity and affect patients' ability to return to work. While open reduction with SL repair is routinely performed to treat PLIs, additional procedures may be considered. Undergoing concurrent CTR in the absence of neurological symptoms showed no differences in outcomes.Level III, retrospective cohort study.
Keywords: perilunate injury; surgical management; outcomes